A Comprehensive Simulation of PEV Penetration Impact on Residential Area Distribution Network - Mangunkusumo, Kevin Gausultan Hadith; Hartono, Joko (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2024)
Nowadays, rapid growth of electric vehicles is one of the breakthroughs for the future. Electrical utility with first stage of EV ecosystem adoption has to prepare for the impact of high demand of PEV penetration especially in residential area. The increase of EVs and charging points are challenge for the grid network. High number of private charging points in residential area is a big future demand that needs to be considered. This study aims to create a comprehensive model of electric vehicle charging penetration impact in residential area with the worst possible conditions and specific data in Indonesia. PEV charging profile and real residential load profile in Indonesia are recorded and used in this study. Driving behavior survey, distribution network modelling and PEV charging profile modelling are constructed. High PEV penetration Feeder loading and voltage drop are evaluated. High PEV penetration would impact on overloading and voltage drop on the network. Peak shifting in distribution network could possibly happen following the EV user charging behavior. However, for the first stage EV ecosystem development, the time shifted strategy including varying the PEV charging location near the transformer could resulting valley filling and reducing the network loses.